Cancer cachexia affects patients with head and neck cancer in all stages of disease: a prospective cross-sectional study (2020)
The aim of the study was to determine the prevalence of cancer cachexia according to the clinical stage and determine differences in body composition, usual energy intake, and proinflammatory profile between cachectic and non-cachectic patients newly diagnosed with head and neck squamous cell carcinoma (HNSCC). A cross-sectional study was conducted in adult patients diagnosed with HNSCC admitted to the oncology unit before starting cáncer treatment. Cancer cachexia was assessed according to Fearon criteria, and patients were divided into two groups: cachectic and non-cachectic patients. Body composition measured by bioelectrical impedance, energy intake, and biochemical and inflammatory markers were assessed. Comparative analyses were performed Student’s-T test, using one-way ANOVA, chi-square and Mann Whitney-U test. Of the 79 consecutive patients included in the analysis, 72% (n¼57; 61 ± 15 years) were classified as cachectic and 28% (n¼22;59 ± 10 years) as non-cachectic. According to clinical stage, the prevalence of cachexia was stage I¼8.8%, stage II ¼ 15.8%, stage III ¼ 33.3% and stage IV ¼ 42.1% (P¼0.564) and phase angle showed to be different between these groups (P<0.05). Body composition showed that fatfree mass and total body water were significantly lower in patients with cachexia (p<0.05). No differences were observed in phase angle, food intake or inflammatory markers between cachectic and non-cachectic patients. Cancer-cachexia is prevalent in all clinical stages in newly diagnosed patients with HNSCC. Early identification of cancer cachexia will allow initiate specialized nutrition support in a timely manner.